Network meta-analysis of treatments for perineal extramammary paget's disease: Focusing on performance of recurrence prevention. - Xiaobin Yuan; Ruizhi Xue; Xiaoming Cao (PLoS ONE)
Introduction Perineal extramammary paget's disease (EMPD) is characterized with high recurrence rate. Although numerous therapeutic measures for this disease have been reported so far, it is unknown whether there is significant difference in their recurrence-preventing efficiency. This study aims to compare the recurrence outcomes of reported perineal EMPD treatments. Methods We searched public databases of for published studies concerning perineal EMPD treatments. After screening by inclusion and exclusion criteria, we extracted the data relevant to recurrence rate, and conducted network meta-analysis (NMA) by using Bayesian random-effects approach. Results Our analysis included 29 previous studies (involving both male and female patients) and 11 treatment designs which are wide local excision (WLE), local excision (LE), Mohs micrographic surgery (MMS), radiotherapy (RT), radical vulvectomy (RV), photodynamic therapy (PDT), lasers (LS), imiquimod, and WLE+RT, WLE+PDT, WLE+LS. Comparing with WLE, the MMS showed significant advantage in reducing recurrence [OR: 0.18 (0.03-0.87)], while none of the rest treatments has statistically significant results. After removing outlier studies, MMS still has the significant advantages [OR: 0.35 (0.11-0.82)], and LE turned to be the treatment with worst performance [OR: 13 (2.50-110)]. Covariance analysis of follow-up length, gender differences, and lesion locations indicated only short follow-up time could affect the recurrence statistics, which tend to conceal the real differences. Funnel plot demonstrated there is no significant small study effect. Conclusion MMS has the best performance on reducing perineal EMPD recurrence, while LE exhibits the worst capability in such regard. Recurrence-preventing abilities of other treatments have no significant difference between each other.